“Bayaaz”, The Memoirs and Diary of Khushal Khan Khattak - Shamal, Rizwan Ullah; Wahid, Qadar (Makhz (Research Journal), 2025)
Khushal Khan Khattak is regarded as a genius and representative figure of Pashto poetry and literature in Asian classical literature due to the comprehensive range of his thematic content. Based on his intellectual diversity, stylistic uniqueness, metrical innovations, and genre experimentation, Khushal Baba holds the distinction of being a pioneer. This research paper attempts to critically and analytically examine one of Khushal Baba’s lesser-known works, commonly referred to as " Bayaz" which is considered one of the earliest examples of diary and memoir subgenres in Pashto autobiographical literature.